Two types of marine controlled source electromagnetic transmitters. (November 2015) - Wang, Meng; Deng, Ming; Zhao, Qingxian; Luo, Xianhu; Jing, Jianen
ABSTRACT: Marine controlled source electromagnetic methods are used to derive the electrical properties of a wide range of sub‐seafloor targets, including gas hydrate reservoirs. In most marine controlled source electromagnetic surveys, the deep‐tow transmitter is used with a long horizontal electric dipole being towed above the seafloor, which is capable of transmitting dipole moments in the order of up to several thousand ampere‐metres. The newly developed deployed transmitter uses two horizontal orthogonal electrical dipoles and can land on the seafloor. It can transmit higher frequency electromagnetic signals, can provide accurate transmission orientation, and can obtain higher signal stacking, which compensates for the shorter source dipole length. In this paper, we present the study, key technologies, and implementation details of two new marine controlled source electromagnetic transmitters (the deep‐tow transmitter and the deployed transmitter). We also present the results of a marine controlled source electromagnetic experiment conducted from April to May 2014 in the South China Sea using both the deep‐tow transmitter and the deployed transmitter, which show that the two types of marine transmitters can be used as effective source for gas hydrate exploration.